Fault Location Techniques in Electrical Power System-A Review - Hui Hwang Goh; Sy yi Sim; Mohamad Amirul Hafiz Mohamed; Abdul Khairi Abdul Rahman; Chin Wan Ling; Qing Shi Chua; Kai Chen Goh (Institute of Advanced Engineering and Science, 2017)
Electric fault is the main challenge in the process of providing continues electric supply. Fault can occur at anytime and anywhere. Due to the fault causes are mainly based on natural disaster or accident. Most fault occurrence hardly predicted nor avoided. Therefore, a quick response fault detection is necessary to ensure that the fault area is maintained to ensure a continuous power supply system. Hence, a system is required to detect and locate the position of the fault in the power system especially in the transmission line and distribution line. This paper will review the type of fault that possibly occurs in an electric power system, the type of fault detection and location technique that are available together with the protection device that can be utilized in the power system to protect the equipment from electric fault.